Left Atrial Longitudinal Strain Parameters Predict Postoperative Persistent Atrial Fibrillation Following Mitral Valve Surgery: A Speckle Tracking Echocardiography Study - Candan, Ozkan; Ozdemir, Nihal; Aung, Soe Moe; Dogan, Cem; Karabay, Can Yucel; Gecmen, Cetin; Omaygenç, Onur; Güler, Ahmet (Echocardiography (Mount Kisco, N.Y.), 2013)
Postoperative atrial fibrillation (POAF) is common after cardiac surgery and is associated with increased morbidity, mortality, and prolonged hospital stay. Speckle tracking echocardiography (STE) has been applied recently for evaluation of LA function. The purpose of this study was to examine whether left atrial longitudinal strain measured by STE is a predictor for the development of POAF following mitral valve surgery for severe mitral regurgitation. We studied 53 patients undergoing mitral valve surgery in sinus rhythm at the time of surgery. Echocardiography with evaluation of LA strain by STE was performed. Detection of POAF was based on documentation of AF episodes by continuous telemetry throughout hospitalization. Patients who did not develop POAF were taken as group 1 and those who had POAF constituted group 2. The echocardiographic and clinical predictors of POAF were investigated. POAF occurred in 28.3% of subjects. Mean age, LAVi and BNP were found higher in group 2 while peak atrial longitudinal strain (PALS) (13.9 ± 3.8% vs. 24.8 ± 7.3%; P < 0.001), peak atrial contraction strain (PACS) (7.6 ± 1.95% vs. 11.3 ± 3.5%; P < 0.001) were significantly lower. By multivariate logistic regression analysis, PALS and LAVi were independent predictor of POAF development. LA longitudinal strain was found to predict POAF in patients undergoing mitral valve surgery. It could be used to better identify patients at greater risk of developing POAF, and thus to guide in risk stratification and to take appropriate intensive prophylactic therapy.